A Review of Matrix Converters in Motor Drive Applications - Annette von Jouanne; Emmanuel Agamloh; Alex Yokochi (Energies)
A matrix converter (MC) converts an AC source voltage into a variable-voltage variable-frequency AC output voltage (direct AC-AC) without an intermediate DC-link capacitance. By eliminating the traditional DC-link capacitor, MCs can achieve higher power densities and reliability when compared to conventional AC-DC-AC converters. MCs also offer the following characteristics: total semiconductor solution, sinusoidal input and output currents, bidirectional power flow and controllable input power factor. This paper reviews the history, recent developments and commercialization of MCs and discusses several technical requirements and challenges, including bidirectional switches, wide bandgap (WBG) opportunities using GaN and SiC, overvoltage protection, electromagnetic interference (EMI) and ride-through in motor drive applications. MC design solutions and operation are discussed, including a comparison of control and modulation techniques as well as the detailed development of space vector modulation (SVM) to provide a deep insight into the control implementation and results. The paper concludes with compelling motor drive innovation opportunities made possible by advanced MCs including fully integrated and multiphase systems. For conventional MCs, size reductions of 30% are reported, as well as efficiencies of 98% and low input current total harmonic distortion of 3–5%.